Small-Signal-Stability Enhancement using a Power-System Stabilizer based on the Cuckoo-Search Algorithm against Contingency N-1 in the Sulselrabar 150-kV System - Djalal, Muhammad Ruswandi; Yunus, Muhammad Yusuf; Setiadi, Herlambang; Krismanto, Awan Uji (Makara Journal of Technology, 2018)
Small-signal stability is one of the main factors limiting power transmission in conventional power systems. This concern is primarily handled by adding damper windings of a synchronous generator and power-system stabilizer (PSS). However, due to the impact of the N-1 contingency, damper windings and a conventional PSS are insufficient to overcome this problem. Proper placement and design of the PSS are crucial for improving stability. One approach to optimizing the placement and tuning of the PSS is to use an artificial-intelligence method. Here, the cuckoo-search algorithm (CSA) is proposed to optimize the PSS tuning and placement. Based on simulation, it is found that a PSS based on the CSA can enhance the system’s small-signal stability. The critical, local, and inter-area modes of the investigated system improve significantly. The oscillatory condition is more highly damped, as indicated by a smaller overshoot and faster settling time. It is also found that the CSA can be used to tune the PSS parameter under an N-1 contingency. From the analytical results of the N-1 contingency condition, optimal tuning of the PSS parameters was obtained, resulting in PSS-placement options for generators 1 to 7 and 12 to 15, producing a minimum damping of 0.611.